Draft Genome Sequence of Terrestrial Streptomyces sp. Strain VITNK9, Isolated from Vellore, Tamil Nadu, India, Exhibiting Antagonistic Activity against Fish Pathogens - Saha, Subhasish; Ishaque, Nabila Mohammad; Burgsdorf, Ilia; Macho, Markéta; Ewe, Daniela; Steindler, Laura; Hrouzek, Pavel; Kannabiran, Krishnan; Saurav, Kumar (Microbiology resource announcements, 2021)
We report the draft genome sequence of Streptomyces sp. strain VITNK9, isolated from a soil sample collected in Vellore District (12.9165°N, 79.1325°E), Tamil Nadu, India, with an assembly size of 7,920,076 bp and 72.7% GC content.